2011
DOI: 10.1051/0004-6361/201117454
|View full text |Cite
|
Sign up to set email alerts
|

POISSON project

Abstract: Context. We present the results of the analysis of low-resolution optical-near IR spectroscopy (0.6-2.4 μm) of a sample (47 sources) of Class I and Class II young stellar objects in the Chamaeleon I and II star-forming clouds. These data are part of the POISSON project (Protostellar Optical-Infrared Spectral Survey On NTT). Aims. The aim of the observations is to determine the accretion luminosity (L acc ) and mass accretion rate (Ṁ acc ) of the sources through the analysis of the detected emission features. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
77
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 75 publications
17
77
1
Order By: Relevance
“…4.4.2 and Table 7), with Class I, Flat, and Class II represented as dots, squares, and triangles, respectively. As already observed by several authors (e.g., Muzerolle et al 1998;Natta et al 2006;Antoniucci et al 2011), L acc increases with L * . In our sample there is a large scatter of L acc /L * values for objects with similar L * values, i.e.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…4.4.2 and Table 7), with Class I, Flat, and Class II represented as dots, squares, and triangles, respectively. As already observed by several authors (e.g., Muzerolle et al 1998;Natta et al 2006;Antoniucci et al 2011), L acc increases with L * . In our sample there is a large scatter of L acc /L * values for objects with similar L * values, i.e.…”
Section: Discussionsupporting
confidence: 84%
“…In this framework, we have undertaken a combined optical/IR unbiased spectroscopic survey on a flux-limited sample of selected Class I/II sources, located in six different nearby clouds (namely Cha I & II, L 1641, Serpens, Lupus, Vela, and Corona Australis; see, Antoniucci et al 2011, hereafter Paper I), using the EFOSC2/SOFI instruments on the ESO-NTT (POISSON: Protostellar Objects IR-optical Spectral Survey On NTT). In Paper I we presented the results of the Cha I & II regions, comparing L acc determinations from the different tracers, and discussing the reliability and consistency of the different empirical relationships considered.…”
Section: Introductionmentioning
confidence: 99%
“…The trend found by Natta et al (2004) shows a good correlation over the whole range of masses from few tens of Jupiter masses to about one solar mass. Our new data confirm the trend found by Natta et al (2004) and reinforce the strength of this line as an accretion indicator, agreeing with the results found by Antoniucci et al (2011), who also tested the reliability of this indicator as accretion tracer.…”
Section: Other Hydrogen Recombination Linessupporting
confidence: 92%
“…This mass accretion rate (Ṁ acc , e.g., Hartmann et al 1998) may be compared to the stellar and disk properties to test the predictions of models of disk evolution. Relations between the accretion luminosity (L acc ) and stellar luminosity (L , e.g., Natta et al 2006;Clarke & Pringle 2006;Rigliaco et al 2011a;Manara et al 2012) and betweenṀ acc and stellar mass (M , e.g., Muzerolle et al 2003;Mohanty et al 2005;Natta et al 2006;Herczeg & Hillenbrand 2008;Antoniucci et al 2011Antoniucci et al , 2014Manara et al 2012;Alcalá et al 2014;Ercolano et al 2014;Frasca et al 2015) are frequently derived to examine the dependence of accretion on the properties of the central star. Accretion has sometimes been found to correlate with age (e.g., Hartmann et al 1998;Sicilia-Aguilar et al 2010;Antoniucci et al 2014), although ages of individual young stars in a given This work is based on observations made with ESO Telescopes at the Paranal Observatory under programme ID 084.C-1095 and 094.C-0913.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also demonstrated that L acc derived from several emission lines measured simultaneously lead to results compatible, although with a larger scatter, with more direct methods (Rigliaco et al 2012;Alcalá et al 2014). Therefore, measuringṀ acc from the luminosity of emission lines is a method that is being extensively used in the literature (e.g., Mohanty et al 2005;Natta et al 2006;Fang et al 2009;Costigan et al 2012;Antoniucci et al 2011Antoniucci et al , 2014Biazzo et al 2014).…”
Section: Introductionmentioning
confidence: 99%